(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
هدفت الدَّراسة إلى معرفة الصّعوبات الإداريّة والبشريّة التي تعترض استخدام تقنيات التّعليم الحديثة وتوظيفها في العمليّة التعليميّة من وجهة نظر عينة من معلِّمي مرحلة التّعليم الأساسيّ في مدينة صافيتا في محافظة طرطوس في الجمهورية العربيّة السوريّة، وفقاً لمتغيرّي الجنس وسنوات الخبرة في التّدريس، ولتحقيق أهداف هذه الدِّراسة استخدمت الباحثة المنهج الوصفي، وذلك من خلال إعداد استبانه تم تطبيقها على مجتمع الدَّراسة وقد بلغ عددهم (75) معلِّم ومعلِّمة وقد توصّلت الباحثة إلى مجموعة من النّتائج أهمّها: لا توجد فروق ذات دلالة إحصائية, بين متوسطات درجات استجابات المدرّسين فيما يتعلّق بالصّعوبات الإداريّة والبشريّة تبعاً لمتغيرّي الجنس وسنوات الخبرة في التّدريس. وكان من أهمّ الصّعوبات التي تعترض استخدام تقنيات التّعليم الحديثة في مرحلة التّعليم الأساسيّ هي: قلّة توافر التّقنيات الحديثة في المدارس، واتجاهات المعلّمين السّلبيّة نحو استخدام الأجهزة التّقنية، وضعف تفاعل التّلامذة في أثناء عرض المعلومات باستخدام تقنيات التّعليم الحديثة. وبناءً على نتائج الدِّراسة اقترحت الباحثة: توفير التّقنيات الحديثة وبرمجياتها في المدارس، وتدريب المدرّسين على كيفية استخدامها وتطويرها، وإجراء دراسات أخرى حول صعوبات توظيف التّقنيات في التّعليم الأساسيّ. this study aimed to know the difficulties of administrative and human resources that hinder the use of techniques modern teaching and employment in the educational process from the viewpoint of a sample of teachers of basic teaching in safita city in the province of Tartous, Syrian Arab Republic, according to the variables of sex and years of experience in teaching, and to achieve the objectives of this study, the researcher used descriptive approach, and through the preparation of a questionnaire was applied to the study population, and their number have reached (75) teachers. a researcher to a range of results including: There are not statistically significant differences between the mean scores of the responses of teachers regarding the difficulties of administrative and human resources according to the variables of sex and years of experience in teaching. The important difficulties in the use of modern technologies in teaching in basic teaching are: the limited availability of new technologies in schools, and teachers negative attitudes towards the use of technical devices, and the weakness of the interaction of the students during the presentation of information by using the techniques modern teaching. Based on the results of the study, the researcher suggests: the provision of modern technologies and software in schools, training teachers on how to use and develop it, and valid studies about difficulties on technology employment at basic teaching.